Dissociative chemisorption of hydrogen molecules on defective graphene-supported aluminium clusters: a computational study - Kumar, Deepak; Govindaraja, Thillai; Krishnamurty, Sailaja; Kaliaperumal, Selvaraj; Pal, Sourav (Physical Chemistry Chemical Physics, 2018)
Using periodic density functional theory-based calculations, in the present study, we address the chemical bonding between aluminium clusters (Al-n, n = 4-8 and 13) and monovacant defective graphene. The adsorption strength of the above-mentioned aluminium clusters is fivefold (approximate to 3 to 5 eV) higher on defective graphene as compared to the earlier reported values on non-defective graphene and BN-doped graphene. The Bader charge analysis and different charge densities reveal that this adsorption is driven by significant charge transfer from the Al clusters to defective graphene. Thus, chemisorbed Al clusters demonstrate high activity towards dissociative adsorption of molecular hydrogen.